Chaotic image encryption algorithm using frequency-domain DNA encoding - Guan, Mengmeng; Yang, Xuelin; Hu, Weisheng (IET image processing, 2019)
A digital image encryption algorithm based on dynamic deoxyribonucleic acid coding and chaotic operations using hyper digital chaos in frequency-domain is proposed and demonstrated, where both the amplitude and phase components in frequency-domain are diffused and scrambled. The proposed encryption algorithm is evaluated through various evaluations of key parameters such as histogram uniformity, entropy, and correlation. Excellent performance of the encrypted image is achieved to resist the statistical attacks, which implies that the statistical properties of the original image are completely destroyed. In the encryption procedure, each cipher pixel is affected by all of the plain-pixels as well as cipher-pixels, due to the implementation of chaotic diffusion and scrambling operations, which increases the sensitivity of the encrypted image to the plain-text, and improves the security against any differential attacks. Moreover, due to the high sensitivity introduced by the hyper digital chaos, a huge key space is provided for the encrypted image to ensure the high security level, thus the encryption algorithm has a strong secure capability against the brute-force attacks.